Using CFIR framework for understanding barriers and facilitators to implementation of community tuberculosis program in Burkina Faso - Donessouné, Flore M. Gisèle; Sossa, Olivier G.; Kouanda, Seni (Frontiers in Health Services, 2024)
In 2020, there were nearly 9.9 million new Tuberculosis cases and 1.3 million deaths, with about 95% occurring in developing nations. Burkina Faso implemented a community Tuberculosis program, involving Civil Society Organizations, to increase screening and improve treatment outcomes. Therefore, this study aims to identify the factors influencing the implementation of community interventions involving these organizations in the fight against TB in Burkina Faso.This qualitative study conducted semi-structured key informant interviews with a purposive sample of health providers from the ministry of health and community health workers. We used framework (the consolidated framework for implementation research was used method to identify barriers and facilitators to implementation of community tuberculosis program in Burkina Faso.A total of 23 interviews were conducted. The results of this research shed light on several key factors that either contributed to or hindered the program's success. Among the facilitating factors, we identified close collaboration between national and international stakeholders, as well as remarkable program flexibility to adapt to local conditions. Furthermore, continuous training and support for community health workers proved crucial for the program's implementation.However, significant challenges were also unveiled. These challenges encompassed insufficient financial resources, difficulties related to the recruitment and management of civil society associations, and issues regarding program ownership at the peripheral level. Additionally, irregular payments to community health workers had a detrimental impact on their motivation and commitment.Our study conducted a comprehensive examination of the obstacles and facilitators encountered in the implementation of a community-based tuberculosis control program in Burkina Faso.The results of this research shed light on several key factors that either contributed to or hindered the success implementation of program. Measures should be taken to mobilize national resources, strengthen the capacities of associations, and promote local ownership of the program. Special attention should also be given to improving financial management and resolving issues related to the recruitment and compensation of community health workers. For such community-based tuberculosis programs to succeed in Burkina Faso and in similar context